2014
DOI: 10.1111/boj.12227
|View full text |Cite
|
Sign up to set email alerts
|

Ovary and ovule anatomy in the nidularioid complex and its taxonomic utility (Bromelioideae: Bromeliaceae)

Abstract: In Bromelioideae, the so-called nidularioid complex contains closely related genera, the circumscription of which has been problematic. The goal of this study was to describe the ovary and ovule anatomy of six species of the nidularioid complex belonging to Canistropsis, Canistrum, Edmundoa, Neoregelia, Nidularium and Wittrockia and to use these characters in a parsimony analysis of relationships. In all analysed species, schizogenous-type aerenchyma is present in the ovarian mesophyll. Edmundoa lindenii has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
15
1
1
Order By: Relevance
“…Anatomical analysis of reproductive organs has been used for taxonomic and phylogenetic purposes in Bromeliaceae and Dyckia (Sajo et al 2005;Fagundes & Mariath 2010;Nogueira et al 2015;Santos-Silva et al 2015), due to not only the descriptive and diagnostic potential but also to the value of this kind of analysis in evolutionary considerations or the relative homogeneity of some often used morphological traits. In Dyckia, in addition to general anatomical traits of the flower (Dorneles et al 2014;Martins et al 2015), stamen anatomy, especially of the anther, has been investigated in some works from ontogenetic (Sajo et al 2005;Mendes et al 2012), taxonomic (Dorneles et al 2014;Martins et al 2015) and histochemical points of view, especially in endemic or rare species.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical analysis of reproductive organs has been used for taxonomic and phylogenetic purposes in Bromeliaceae and Dyckia (Sajo et al 2005;Fagundes & Mariath 2010;Nogueira et al 2015;Santos-Silva et al 2015), due to not only the descriptive and diagnostic potential but also to the value of this kind of analysis in evolutionary considerations or the relative homogeneity of some often used morphological traits. In Dyckia, in addition to general anatomical traits of the flower (Dorneles et al 2014;Martins et al 2015), stamen anatomy, especially of the anther, has been investigated in some works from ontogenetic (Sajo et al 2005;Mendes et al 2012), taxonomic (Dorneles et al 2014;Martins et al 2015) and histochemical points of view, especially in endemic or rare species.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and anatomical studies using diff erent approaches have provided effective instruments for characterization of species and elucidation of taxonomic and phylogenetic problems in Bromeliaceae (Varadarajan & Gilmartin 1987;Benzing 2000;Sajo et al 2004;Proença & Sajo 2007;Santos-Silva et al 2015;Nogueira et al 2015), a predominantly neotropical diverse family. Given the structural complexity of reproductive organs in this taxon, morphological studies of diff erent fl ower organs have allowed for inferences of evolutionary, systematic, ecological and physiological orders in diverse genera of the family (Varadarajan & Brown 1988;Brown & Gilmartin 1989;Brown & Terry 1992;Sajo et al 2004;Fagundes & Mariath 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these features have been used in a taxonomic approach, e.g. Fagundes & Mariath (2014) reviewed the female gametophyte and ovule in Bromeliaceae and Nogueira et al (2015) showed ovary and ovule features in nidularioids. Fagundes & Mariath (2014) reviewed the female gametophyte and ovule in Bromeliaceae and Nogueira et al (2015) showed ovary and ovule features in nidularioids.…”
Section: Introductionmentioning
confidence: 99%